Dynamic reliability assessment for bilateral contract electricity providers in restructured power systems - Ding, Yi (2011)
This paper presents a new method to evaluate dynamic reliability indices for bilateral contract electricity providers in restructured power systems. The proposed method is based on the combination of stochastic processes methods and the universal generating function technique. It can provide dynamic reliability assessment for bilateral providers in restructured power systems. In the proposed method, generating units are represented as multi-state models (up to 10 states and more), which are more accurate than the conventional binary-state models. To avoid the “dimension damnation” problem caused by solving the stochastic process model of the entire system, only the stochastic model for each unit is solved. The state probabilities for the bilateral contract electricity provider and the corresponding reliability indices are evaluated by using simple algebraic operations based on the universal generating function technique. Moreover, techniques for the reliability evaluation of bilateral contract electricity provider considering reserve agreements with other generation companies are also proposed in this paper. An example considering different types of generating units from industry is used to illustrate the proposed method.